Coming of Age in Iran : Poverty and the Struggle for Dignity - Hashemi, Manata; Hashemi, Manata (Book collections on Project MUSE., 2020)
An inside look at young Iranians navigating poverty and stigma in a time of crisis In Coming of Age in Iran, Manata Hashemi takes readers inside the lives of Iranian youth. Drawing on first-hand accounts, Hashemi shows how the young Iranian men and women known as the "burnt generation"--those between the ages of 15 and 29, who came of age after Iran's 1979 Islamic Revolution--face their future prospects.With a compassionate eye, Hashemi paints a nuanced portrait of their day-to-day struggles in Iran. Hashemi spent months with these youth, observing them at bazaars, hair salons, parks, and mosques, tutoring them in English and sharing meals in their family homes. Many young Iranian men and women are jobless, living with their parents, and delaying marriage, ultimately failing to meet what they consider the traditional benchmarks of adulthood. Hashemi follows their stories, one by one, as they try to climb up the proverbial ladder of success.Coming of Age in Iran sheds light on the inner lives of a new generation of Iranian youth as they struggle in the face of ongoing economic crisis.